Consistent assessment of neutron-induced activation of 93Nb - Avrigeanu, Vlad; Avrigeanu, Marilena (Frontiers in Physics, 2023)
A concurrent suitable account of excitation functions for various reaction channels, at variance with TALYS-1.96 as well as TENDL-2021 results is concerned by paying more attention to use of consistent parameter sets that are formerly obtained or validated by analysis of other independent data. No empirical rescaling factors of the γ and/or neutron widths have been used, while this approach is the only possible for current large-scale data evaluations performed by TALYS and completed within TENDL. On the other hand, detailed analyses based on consistent input parameter sets are really needed to eventually improve the global parameters to be then adopted within large-scale evaluations. At the same time, a proper account in this work of all available data for competitive reaction channels prevented compensation effects of less accurate model parameters from happening. Remaining questions are emphasized as well as the need for additional measurements.